2021
DOI: 10.21203/rs.3.rs-177769/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Morbidity and Mortality Rates of Boer and Central Highland Goats at Ataye Crossbreeding Program Research Site: Non-parametric Survival Analysis and Piecewise Exponential Model

Abstract: Non-parametric survival analysis and piecewise exponential model (PEM) was used to estimate prevalence and incidence of goat mortality, to identify major clinical causes of morbidity and mortality related disease, and to investigate animal and environmental related risk factors affecting goat mortality at Ataye boer goat breeding and evaluation research site. A total of 671 kids and 347 adult (yearling) age goats were used for the analysis of non-parametric survival and piecewise exponential model for survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…This is consistent with previous studies that showed the Boer breed had poor survival rates compared to other breeds in different countries and regions. For example, Tesema et al [37] and Tessama et al [38] reported that the Boer breed had higher mortality rates than the local Ethiopian breeds. Harrison [39] showed that Boer and its crosses with Kiko had higher mortality rates compared to purebred Kiko breed in the US.…”
Section: Risk Factors Associated With Pre-weaning Mortalitymentioning
confidence: 99%
“…This is consistent with previous studies that showed the Boer breed had poor survival rates compared to other breeds in different countries and regions. For example, Tesema et al [37] and Tessama et al [38] reported that the Boer breed had higher mortality rates than the local Ethiopian breeds. Harrison [39] showed that Boer and its crosses with Kiko had higher mortality rates compared to purebred Kiko breed in the US.…”
Section: Risk Factors Associated With Pre-weaning Mortalitymentioning
confidence: 99%